Participatory risk analysis to ensure food safety of edible offal from game meat - Ramrajh, S.; McCrindle, C.M.E.; Heeb, A.W.; Makita, K.; Grace, Delia (2011)
BACKGROUND: The meat obtained from trophy hunting, culling and harvesting indigenous game animals has been used in the past by biltong (traditional dried meat) hunters, local butchers and for export markets. The edible by-products, currently discarded, could be used as a renewable source of protein in low income communities. Constraints to the utilization of such edible by-products of game meat include lack of recognized food value chains in informal markets, food safety concerns and limited market access to edible by-products from game harvesting operations. METHODS: Participatory risk analysis was used to investigate the feasibility of using edible offal as a source of renewable protein, to address food security issues in poor communities bordering game parks in South Africa. The market outlet for the food value chain selected for investigation, was informal markets in Pongola, KwaZulu Natal, South Africa. In order to promote food safety, only edible offal from impala carcasses that had been through primary meat inspection, were considered during the study. Samples were submitted for microbiology, in line with published EU guidelines and Veterinary Procedural Notices to an accredited laboratory. Structured and informal interviews were held with stakeholders, including veterinarians, game harvesters and informal traders. Scenario planning and decision tree analysis was used to develop a practical food marketing chain and estimate critical control points for identified physical, biological and chemical hazards. In addition, environmental risks were considered and a risk mitigation strategy designed, to reduce any possible environmental impacts. It was concluded that the food marketing chain is feasible and that the current practice of leaving the offal for predators.